Physospermopsis deqinensis (Apiaceae), a new species from Yunnan, China - Guo, Xian-Lin; Xu, Xin-Rui; Gou, Wei; Zhou, Song-Dong; He, Xing-Jin (Phytotaxa, 2026)
Physospermopsis deqinensis X.L.Guo & X.J.He, a new species from Deqin County, Yunnan, China, is described and illustrated. It resembles P. rubrinervis and P. shaniana by having leaf-like bracts and bracteoles with purplish margins, but differs in its stems 3–5 mm thick, pinnately divided bracts, longer bracteoles, umbels with 13–20 rays, and oblong to ovoid mericarps with linear, slightly sinuate ribs. The new species also has more vittae per furrow (3–4) and an irregular endosperm that is ventrally concave and dorsally undulate. Phylogenetic analyses using nrITS and plastid introns (rpl16, rps16) place P. deqinensis as sister to the clade comprising P. delavayi and P. alepidioides in the nuclear tree, and sister to a clade of six Physospermopsis species in the plastid tree. The species is currently known only from the Biluo Snow Mountains, Yunnan, and is preliminarily assessed as Data Deficient (IUCN).